Pengaruh Penggunaan Sistem Informasi Manajemen Keuangan Terhadap Kualitas Laporan Keuangan Pada Yayasan Daar El Haq Sejahtera - Nk, Silvia Rizqiya Fauja; Arafat, Fauzi (Sekretariat Pusat Lembaga Komunitas Informasi Teknologi Aceh, 2025)
The development of the digital era requires non-profit organizations, including foundations, to adopt information technology in financial management to improve accuracy and transparency. This study aims to analyze the effect of the implementation of the Financial Management Information System on the quality of financial statements at the Daar El Haq Sejahtera Foundation. This study uses a quantitative approach with a simple linear regression analysis method. Data collection was carried out through questionnaires distributed to 30 foundation employees involved in financial management. The results of the analysis show that the implementation of the Financial Management Information System has a positive and significant effect on the quality of financial statements, which includes aspects of relevance, reliability, understandability, and comparability. Optimal system implementation has the potential to improve accountability and transparency in the foundation's financial reporting process. These findings can be the basis of recommendations for other foundations in adopting information technology to improve effectiveness and efficiency in financial management.